Intrinsically radiolabelled [(59)Fe]-SPIONs for dual MRI/radionuclide detection - Hoffman, David (e-Century Publishing Corporation, 2014)
Towards the development of iron oxide nanoparticles with intrinsically incorporated radionuclides for dual Positron Emission Tomography/Magnetic Resonance Imaging (PET/MRI) and more recently of Single Photon Emission Computed Tomography/Magnetic Resonance Imaging (SPECT/MRI), we have developed intrinsically radiolabeled [(59)Fe]-superparamagnetic iron oxide nanoparticles ([(59)Fe]-SPIONs) as a proof of concept for an intrinsic dual probe strategy. (59)Fe was incorporated into Fe(3)O(4) nanoparticle crystal lattice with 92±3% efficiency in thermal decomposition synthesis. Multidentate poly(acrylic acid)-dopamine-poly(ethylene-glycol-2000) (PAA-DOP-PEG) ligands were designed and synthesized based on facile EDC chemistry and utilized to functionalize the [(59)Fe]-SPIONs. The transverse relaxivity of [(59)Fe]-SPIONs (97±3 s(-1)mM(-1)) was characterized and found to be similar to non-radioactive SPIONs (72±10 s(-1)mM(-1)), indicating that (59)Fe incorporation does not alter the SPIONs’ MRI contrast properties. [(59)Fe]-SPIONs were used to evaluate the nanoparticle biodistribution by ex vivo gamma counting and MRI. Nude mice (n=15) were injected with [(59)Fe]-SPIONs and imaged at various time points with 7T small animal MRI scanner. Ex vivo biodistribution was evaluated by tissue-based gamma counting. MRI signal contrast qualitatively correlates with the %ID/g of [(59)Fe]-SPIONs, with high contrast in liver (45±6%), medium contrast in kidneys (21±5%), and low contrast in brain (4±6%) at 24 hours. This work demonstrates the synthesis and in vivo application of intrinsically radiolabeled [(59)Fe]-SPIONs for bimodal detection and provides a proof of concept for incorporation of both gamma- and positron-emitting inorganic radionuclides into the core of metal based MRI contrast agent nanoparticles.